Factors Affecting Career Longevity of Female Plastic Surgeons in Academia: A Qualitative Ethnographic Pilot Study - Aditi M. Kanth, MD; Joowon Choi, MD; Marita Martiney, PhD; Meera Reghunathan, MD; Katerina Gallus, MD; Wendy Chen, MD, MS (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. More women are training in plastic surgery, but representation in academia continues to lag, with female plastic surgeons being more likely than their male counterparts to leave academia for another practice type. The aim of the study was to understand why women enter and leave academia. Methods:. The American Society of Plastic Surgeons Women in Plastic Surgery listserv was solicited for volunteers. Interviewees were selected based on demographics (seniority, region, race, sexual orientation, practice type) to represent a diverse cohort. In accordance with ethnographic qualitative research methods, interviews discussed experiences during training, first job selection and departure, and workplace culture. Responses were anonymized and reported in aggregate. Results:. From 184 respondents, 22 practicing surgeons were selected: 7 in academia, 8 in private practice, and 7 who had left academia. Practice content was more important to those initially choosing academia (50% versus 37.5%), whereas supportive environment and location were more important to those in private practice. Women who stayed in academia were more likely to have female mentorship than those who left (42.8% versus 14.2%). Those who left academia cited perceived gender inequity (85.7%) and lack of flexibility (71.4%). Current satisfaction with workplace culture was highest in the nonacademic practice group (87% extremely or very satisfied). Conclusions:. Factors influencing why female plastic surgeons enter and leave academia include mentorship, practice content, location, and workplace culture. These rich qualitative data are currently being used to design a validated survey tool to further elucidate factors contributing to women leaving academia and propose meaningful solutions.